UJI AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT JERUK SUNKIST MUDA DAN TUA DENGAN METODE DPPH - Pedro Shane M Simbolon (ADISAM PUBLISHER, 2026)
Sunkist orange (Citrus sinensis L.) is known to contain various secondary metabolites such as flavonoids, phenols, essential oils, tannins, terpenoids, and steroids, which contribute to its biological activities, particularly as antioxidants. This study aimed to evaluate and compare the antioxidant activity of young and mature Sunkist orange peel extracts using the DPPH (2,2- diphenyl-1-picrylhydrazyl) method. Peel samples were extracted via maceration with 96% ethanol, and antioxidant activity was measured at concentrations of 5, 10, 20, and 40 ppm, with vitamin C (0.5, 1, 2, and 4 ppm) serving as the positive control. The results indicated that antioxidant activity increased with concentration. The IC₅₀ values obtained were 114.73 ppm for young peel extract, 54.32 ppm for mature peel extract, and 7.10 ppm for vitamin C. Based on these results, young peel extract exhibited moderate antioxidant activity, while mature peel extract demonstrated strong antioxidant activity. The higher antioxidant capacity of mature peel is likely associated with increased flavonoid and phenolic content during ripening. These findings highlight the potential of mature Sunkist orange peel, often regarded as agricultural waste, as a sustainable natural source of antioxidants for pharmaceutical and food applications.